Characterization of Indigenous Arbuscular Mycorrhizal Fungi in Seedlings and Production of Pepper (Piper nigrum L.) Cultivation - Hajoeningtijas, Oetami Dwi; Mardatin, Noor Faiqoh; Suyadi, Aman; Ma'ruf, Fajar (Journal of Tropical Mycorrhiza, 2024)
Mycorrhizal plants are known to be only slightly attacked by diseases caused by fungi. This condition can be used as an alternative to control biological diseases in pepper plants. The study was conducted to explore the diversity of arbuscular mycorrhizal fungi in pepper plants in nursery and production areas, which have the potential to be used as biological agents in controlling stem rot disease caused by Phytophthora sp. fungi. Samples were taken from three fields in Kedarpan Village, Kejobong District, Purbalingga Regency. The study was a survey experiment that took samples intentionally (purposive sampling). ata on the intensity of root infection to determine its diversity were analyzed using Analysis of Variant. Data from several observation variables will be analyzed descriptively, qualitatively, and quantitatively. Morphospecies identification was carried out on spores of Arbuscular Mycorrhizal Fungi that were successfully isolated. Arbuscular Mycorrhizal Fungi that were successfully isolated and identified from pepper plantations consisted of 5 genera of fungi, with morphospecies diversity in each genus. In the pepper nursery land, there were the genera Glomus, Gigaspora, Acaulospora, and Entropospora; the pepper production land of the Margo Utomo Farmers Group had the genera Glomus, Gigaspora, Scutellospora, and Entropospora; while the pepper production land owned by residents had Glomus, Gigaspora, and Entropospora. Glomus was found at all sampling locations. The level of infection or colonization of AMF in pepper plantations in the three locations observed showed a high level of infection (>30%). However, in each pepper plantation area, AMF did not significantly affect the intensity of root infection (F = 6.114; p = 0.003).